Warm temperature stimulus suppresses the perception of skin wetness during initial contact with a wet surface. Issue 1 (14th February 2014) - Filingeri, D.; Redortier, B.; Hodder, S.; Havenith, G.
<x xml:space="preserve">Abstract</x> Background/purpose In the absence of humidity receptors in human skin, the perception of skin wetness is considered a somatosensory experience resulting from the integration of temperature (particularly cold) and mechanical inputs. However, limited data are available on the role of the temperature sense. Methods Wet and dry stimuli at 4°C and 8°C above local skin temperature were applied on the back of seven participants (age 21 ± 2 years) while skin temperature and conductance, thermal and wetness perceptions were recorded. Results Resting local skin temperature was always increased by the application of the stimuli (+0.5–+1.4°C). No effect of stimulus wetness was found on wetness perceptions (P > 0.05). The threshold (point '−2 slightly wet' on the wetness scale) to identify a clearly perceived wetness was never reached during any stimulations and participants did not perceive that some of the stimuli were wet. Overall, warm temperature stimuli suppressed the perception of skin wetness. Conclusion We conclude that it is not the contact of the skin with moisture per se, but rather the integration of particular sensory inputs (amongst which coldness seems dominant) which drives the perception of skin wetness during the initial contact with a wet surface.